2022
DOI: 10.1155/2022/2180214
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internal Heat Acupuncture Combined with High-Voltage Long-Duration Pulsed Radiofrequency on Subacute Postherpetic Neuralgia: A Retrospective Study

Abstract: Objectives. This study aims at investigating the internal heat acupuncture (IHA) combined with the high-voltage long-duration pulsed radiofrequency (PRF) therapeutic effect on subacute postherpetic neuralgia (PHN). Methods. This retrospective study comprised 81 cases with PHN. They were divided into three groups: IHA combined with the high-voltage long-duration PRF group (IHA-PRF), intradermal injection combined with the high-voltage long-duration PRF group (II-PRF), and the high-voltage long-duration PRF grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have shown that prompt clinical interventions in patients with acute or subacute herpes zoster neuralgia can prevent and alleviate post-herpetic neuralgia. [11] However, given its complex mechanism and challenging treatment, post-herpes neuralgia still lacks standardization. Currently, there have been scarce large-scale studies confirming the effectiveness of traditional surgical interventions, including semilunar ganglion radiofrequency, in treating herpes zoster neuralgia within the trigeminal nerve branch distribution area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that prompt clinical interventions in patients with acute or subacute herpes zoster neuralgia can prevent and alleviate post-herpetic neuralgia. [11] However, given its complex mechanism and challenging treatment, post-herpes neuralgia still lacks standardization. Currently, there have been scarce large-scale studies confirming the effectiveness of traditional surgical interventions, including semilunar ganglion radiofrequency, in treating herpes zoster neuralgia within the trigeminal nerve branch distribution area.…”
Section: Discussionmentioning
confidence: 99%
“…Combining treatments with diverse targeting mechanisms is believed to result in a more effective therapeutic response for ZAP. For example, combinations such as DRG pulsed radiofrequency with steroids, ozone, local anesthetics or recombinant human interferon-a2b, as well as pulsed radiofrequency combined with continuous radiofrequency or heat acupuncture are applied for ZAP [38][39][40][41][42][43][44][45][46]. Numerous clinical studies have focused on the combination of pulsed radiofrequency and ozone, consistently demonstrating the safety and effectiveness of this treatment modality [40][41][42][43].…”
Section: Combined Treatmentmentioning
confidence: 99%